Movement variability in the golf swing of male and female skilled golfers - Horan, S. A.; Evans, K.; Kavanagh, J. J. (Medicine & Science in Sports & Exercise, 2011)
Background: Despite the complexity of movement, the swings of skilled golfers are considered to be highly consistent. Interestingly, no direct investigation of movement variability or coupling variability during the swings of skilled golfers has occurred. Purpose: To determine whether differences in movement variability exist between male and female skilled golfers during the downswing of the full golf swing. Methods: Three-dimensional thorax, pelvis, hand, and clubhead data were collected from 19 male (mean ± SD: age = 26 ± 7 yr) and 19 female (age = 25 ± 7 yr) skilled golfers. Variability of segmental movement and clubhead trajectory were examined at three phases of the downswing using discrete (SD) and continuous analyses (spanning set), whereas variability of intersegment coupling was examined using average coefficient of correspondence. Results: Compared with males, females exhibited higher thorax and pelvis variability for axial rotation at the midpoint of the downswing and ball contact (BC). Similarly, thorax-pelvis coupling variability was higher for females than males at both the midpoint of the downswing and BC. Regardless of thorax and pelvis motion, the variability of hand and clubhead trajectory sequentially decreased from the top of the backswing to BC for both males and females. Conclusions: Male and female skilled golfers use different upper body movement strategies during the downswing while achieving similarly low levels of clubhead trajectory variability at BC. It is apparent that the priority of skilled golfers is to progressively minimize hand and clubhead trajectory variability toward BC, despite the individual motion or coupling of the thorax and pelvis.